Carbon Stock of Pinus roxburghii Sarg. in Siwalik Foot Hills of Jammu - Joshi, Kuldeep; Sehgal, Sandeep; Gupta, Meenakshi; Upadhyay, Lalit; Shrivastava, Varun (International Journal of Economic Plants, 2022)
The present study was carried out in the year 2021 to estimate the biomass and Carbon stock of Pinus roxburghii. Ten quadrates of size 20×20 m2 were laid out randomly. Diameter at breast height (dbh) and tree height was measured as the primary data. The regression equation √V=0.05131+3.98598D–1.0245√D was used for determining the mean stem volume. The mean tree density, mean tree diameter, mean tree height and mean stem volume at the study site were 150 trees ha-1, 51.21 cm, 19.79 m and 157.17 m3 ha-1, respectively. Similarly, above ground biomass density (AGBD), below ground biomass density (BGBD), total biomass density (TBD) and total carbon density (TCD) at the study site was 93.99 Mg ha-1, 26.32 Mg ha-1, 120.30 Mg ha-1 and 56.54 Mg ha-1, respectively. Average eCO2 was 207.51 Mg ha-1. Average soil bulk density was 1.39 gm cm-3, soil ph 6.47, EC 0.13, SOC 6.31 gm kg-1, NPK 201.44 Mg ha-1, 26.50 Mg ha-1 and 56.66 Mg ha-1,respectively. The soils in the site were almost clay with average percent of sand, silt and clay as 32.44, 30.99 and 36.57, respectively.